Examining the effects of different English speech varieties on an L2 academic listening comprehension test at the item level. (October 2021) - Shin, Sun-Young; Lee, Senyung; Lidster, Ryan
In this study we investigated the potential for a shared-first-language (shared-L1) effect on second language (L2) listening test scores using differential item functioning (DIF) analyses. We did this in order to understand how accented speech may influence performance at the item level, while controlling for key variables including listening passages, item type, and the degrees of intelligibility, comprehensibility, and speaker accentedness. A total of 386 undergraduate and graduate students from China, Korea, and India, who were enrolled in a university in the United States, each took two listening tests. In the first session, they took a standardized listening comprehension test comprising texts recorded by native English speakers. In the second session, they took a listening comprehension test consisting of counterbalanced sets of American English-, Indian-, and Chinese-accented lectures. The results show that the shared-L1 effect is minimal. Effects are consistent for only a few narrow, detail-oriented items, on which Chinese and Korean listeners performed relatively poorly when listening to Indian speakers.